The Cost of Fire : An Economic Analysis of Indonesia’s 2015 Fire Crisis - Glauber, Ann Jeannette (World Bank, Jakarta, 2016)
In a five-month period, man-made fire cost Indonesia $16.1 billion or 2 percent of GDP in 2015. An estimated 2.6 million hectares – an area four times the size of Bali – burned. While the 2015 fires were some of the worst in recent years (in part as a result of el Nino), they are by no means a singular event. Wide-scale fire crises occur annually in Indonesia. Indonesia’s fire story is not just one of loss and damage; fires contribute to significant economic upside for a diverse, if concentrated, group of actors. However, the majority of Indonesians suffer as a result of the economic and physical damage. This document provides a loss and damage analysis of the 2015 fires and explores not just economic costs, but environmental costs as well. It also looks at the important role that fire plays in commodity crops, particularly oil palm, and the actors who benefit.